A linguagem nos anos iniciais do ensino fundamental: contribuições de Vigotski a uma pedagogia da significação - BASTO, Marli Pantoja (2019)
The present work had as objective to analyze the learning of the language in the initial years of the elementary school, focusing on the contributions of Vygotsky based on a pedagogy of signification, in a 1st grade of Elementary School. In a specific sense, it was sought at first to make a theoretical analysis about Vygotsky's contributions to this pedagogy of signification, to understand this process, investigating the practices of language teaching (reading and writing) in the early years and its relation with everyday knowledge / previous knowledge of children, as well as researching the affective and emotional manifestations that occur in the relationships of language learning (reading and writing) and identify the characteristics of a pedagogy of meaning. The research was developed using bibliographical analysis and field research as methodology. Thus, it was verified from the theoretical references that we are symbolic subjects, that we are constituted in the social relations, mediated by the language and the signification and that the school is fundamental in this process, because it is in the school that the child learns the language, the reading and writing. The teacher must then teach in a contextualized way, transforming the relation of knowledge into an affective relationship, without disregarding the prior knowledge of the learner, since knowledge becomes significant only when it contextualizes itself.